2017
DOI: 10.5194/essd-9-251-2017
|View full text |Cite
|
Sign up to set email alerts
|

Basin-scale water-balance dataset (BSWB): an update

Abstract: Abstract. This paper presents an update of a basin-scale diagnostic dataset of monthly variations in terrestrial water storage for large river basins worldwide (BSWB v2016, doi:10.5905/ethz-1007. Terrestrial water storage comprises all forms of water storage on land surfaces, and its seasonal and inter-annual variations are mostly determined by soil moisture, groundwater, snow cover, and surface water. The dataset presented is derived using a combined atmospheric and terrestrial water-balance approach with con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Such a belief springs, in part, from the fact that amplitudes of internal ocean variability in intra-and interannual mass that GRACE observes are relatively mute in comparison to on-land hydrology, two-way land-to-ocean transport, and secular trends in land ice changes (Chambers, 2006;Chambers and Willis, 2008;Watkins et al, 2015;Wiese et al, 2016;Save et al, 2016). In fact, Hsu and Velicogna (2017) have used ocean-bottom pressure data, in conjunction with space geodetic data, to claim that fingerprints associated with decadal-scale on-land mass changes are detected. Furthermore, Davis and Vinogradova (2017) have shown that the fingerprints of Greenland ice mass loss have had measurable influences on tide gauge records along the eastern coast of the US since the mid-1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Such a belief springs, in part, from the fact that amplitudes of internal ocean variability in intra-and interannual mass that GRACE observes are relatively mute in comparison to on-land hydrology, two-way land-to-ocean transport, and secular trends in land ice changes (Chambers, 2006;Chambers and Willis, 2008;Watkins et al, 2015;Wiese et al, 2016;Save et al, 2016). In fact, Hsu and Velicogna (2017) have used ocean-bottom pressure data, in conjunction with space geodetic data, to claim that fingerprints associated with decadal-scale on-land mass changes are detected. Furthermore, Davis and Vinogradova (2017) have shown that the fingerprints of Greenland ice mass loss have had measurable influences on tide gauge records along the eastern coast of the US since the mid-1990s.…”
Section: Introductionmentioning
confidence: 99%
“…A basin-scale diagnostic dataset of monthly variations in terrestrial water storage of large river basins (BSWB v2016) was taken to examine the multi-year balance of the Yangtze River Basin above Yichang gauge, where the QYJ Basin was included. This dataset was produced based on atmospheric and terrestrial water balances with streamflow measurements and reanalysis atmospheric moisture [34,35]. This dataset indicated that the Yangtze River Basin was relatively weak in annual variation during the period of 1979-1986 (multi-year averagely below 1.0 mm yr −1 ).…”
Section: Uncertainties In the Precipitation Estimationmentioning
confidence: 99%
“…Here, we aim to use such estimates to also evaluate the quality of the reconstruction during the period when no GRACE data are available (i.e., prior to 2002). We evaluate TWS products using a recently updated basinscale water balance dataset (BSWB) (Hirschi and Seneviratne, 2017), which covers 341 catchments and is based on ERA-Interim reanalysis data (Dee et al, 2011) and runoff observations from the Global Runoff Data Centre (GRDC). The temporal coverage of BSWB estimates at each river basin thus depends on the availability of runoff data and does not always cover the GRACE time period.…”
Section: Comparison With De-seasonalized Basin-scale Water Balancementioning
confidence: 99%